HYGIOMANIA: ANALYSIS OF MEDIA INFLUENCE ON HEALTH CONCEPTIONS (Fiep Bulletin - online, 2012)
The students' participation in High School classes is one of the biggest challenges in school physical education. It isthe phase of formal education which, according to guidelines law, aims to broaden and deepen the knowledge, create a criticalsense and prepare students for work as well. However, as a matter of fact, it is observed that the contents are narrowing in the fourclassic team sports. The main objective of this study is to identify the relation between the contents and the students' participation in High School physical education. It is justified by the fact that the large number of students who evade the classes in this periodof basic education. This study is characterized as a field research, descriptive and exploratory. The interviewed group wascomposed of students and teachers of physical education of three grades of high school in three shifts of private schools, schoolsfrom the state of Rio de Janeiro and schools from the municipality of Queimados. The sample was consisted of one hundredstudents and three teachers working in the observed classrooms. The data collection instrument was a questionnaire validatedand applied by signing the consent form. It was concluded in the discourse that there was no resistance from the interviewedstudents to other different contents. The discipline is based on the ability in sports and the classic presentation of theoreticalstudies. The presented expectation is that the classes could be different, a fact that identifies the repetition of content alreadyworked in elementary school, without further deepening. These factors reinforce the decline in participation by high schoolstudents. In relation to the night shift, there is a type of behavior that is observed by the school and teachers that reinforces thedevaluation of the discipline practice.
Keywords: hygiomania; media; health concept